ASSOCIATION BETWEEN ENTERAL NUTRITION AVAILABILITY WITH NUTRITIONAL FULFILLMENT AND NUTRITIONAL STATUS IN HEAD AND NECK CANCER PATIENTS - Marvin Marino; Diyah Eka Andayani; Angela Giselvania (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2022)
Background: The availability of enteral nutrition is one of nutritional intervention that can be given to prevent a decrease in nutritional intake and nutritional status in HNC patient. Research objective: This study aims to see the correlation between the availability of enteral nutrition with nutritional fulfillment and nutritional status. Methodology: A cross sectional study was conducted on adult subjects with HNC after radiation therapy at the RSCM radiotherapy outpatient clinic. Nutritional fulfillment was assessed by semi-quantitative FFQ while nutritional status was measured by calculating body mass index (BMI). Research results: Forty-one subjects mean age of 51 years participated in the study. The mean BMI of subjects with enteral nutrition was lower than those on oral nutrition, 18,2±2,6 kg/m2 compared to 21,2±3,5 kg/m2 respectively. The mean total energy intake of subjects with enteral nutrition route was higher, which was 1498,1±430,6 Kcal/day compared to 1291,4±393,3 Kcal/day. There was a moderate negative correlation between the availability of enteral nutrition and nutritional status (r=-0,346, p=0,027), meanwhile there was a weak positive correlation with nutritional fulfillment (r=0,216, p=0,174). However, in this study we found that the proportion of subjects with enteral nutrition who experienced a decrease in BMI was less than the proportion of subjects on the oral route, which was 22,2% compared to 43,8% respectively. Conclusion: There is a moderate negative correlation between the availability of enteral nutrition with nutritional status and a weak positive correlation with nutritional fulfillment which is still influenced by confounding factors.